2017
DOI: 10.1016/j.sjbs.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial and antifungal activities of flowerhead and root essential oils of Santolina chamaecyparissus L., growing wild in Tunisia

Abstract: The antimicrobial properties of essential oil from various species have not been investigated enough in the previous studies dealing with the biological activities of medicinal plants. In Tunisia, L. (Asteraceae) is the only species recorded and is used as vermifuge and emmenagogue. The chemical composition, antibacterial and antifungal properties of essential oils from the flowerheads and roots of spontaneous growing in Tunisia and the chemical composition which leads to the Tunisian chemotype are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…chamaecyparissus are 1,8‐cineole (11.2%) and spathulenol (7.6%) . However, the hydrodistilled oil of this species shows an enormous chemical variability, and some oils are rich in artemisia ketone (27 – 38%) and β ‐phellandrene (9 – 22%) [ ][ ] or in camphor (31.1%) …”
Section: Resultsmentioning
confidence: 99%
“…chamaecyparissus are 1,8‐cineole (11.2%) and spathulenol (7.6%) . However, the hydrodistilled oil of this species shows an enormous chemical variability, and some oils are rich in artemisia ketone (27 – 38%) and β ‐phellandrene (9 – 22%) [ ][ ] or in camphor (31.1%) …”
Section: Resultsmentioning
confidence: 99%
“…The Mediterranean and semi-arid climate of this country favors the growth of various types of wild plants whose valorization is under-exploited. Some of them, such as Artemisia campestris L., Lavandula stoechas L., Origanum glandulosum, Pelargonium graveolens ., are known for their anti-diabetic effects in traditional medicine (1) while others have been recognized as having anti-bacterial effects (Santolina chamaecyparissus L.) (2) or herbicide effects (Pinus nigra) (3) . The valorization of all these natural resources is mainly based on the extraction of volatile molecules, called "essential oils" whose composition determines their usefulness for medicinal, cosmetic or food applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among of them , αcadinol, showed selective toxicity against human colon adenocarcinoma cells (Sylvestre et al, 2006) (He et al, 1997). Otherwise, it was reported that the essential oils extracted from other medicinal plants containing αpinene, p-cymene , α-copaene and δ-cadinene as volatile components have a potential antimicrobial and antifungal activities (Bel Hadj Salah-Fatnassi et al, 2017).…”
Section: Effect Of the Extraction Methods On The Chemical Compositionmentioning
confidence: 99%